Individualising dual antiplatelet therapy after percutaneous coronary intervention: the IDEAL-PCI registry. Issue 10 (31st October 2014) - Christ, Günter; Siller-Matula, Jolanta M; Francesconi, Marcel; Dechant, Cornelia; Grohs, Katharina; Podczeck-Schweighofer, Andrea
Abstract : Objective: To evaluate the clinical utility of individualising dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) in an all-comers population, including ST-elevation myocardial infarction (STEMI) patients. Setting: Tertiary care single centre registry. Participants: 1008 consecutive PCI patients with stent implantation, without exclusion criteria. Intervention: Peri-interventional individualisation of DAPT, guided by multiple electrode aggregometry (MEA), to overcome high on-treatment platelet reactivity (HPR) to ADP-induced (≥50 U) and arachidonic acid (AA)-induced aggregation (>35 U). Outcome measures: The primary efficacy end point was definite stent thrombosis (ST) at 30 days. The primary safety end point was thrombolysis in myocardial infarction (TIMI) major and minor bleeding. Secondary end points were probable ST, myocardial infarction, cardiovascular death and the combined end point: major cardiac adverse event (MACE). Results: 53% of patients presented with acute coronary syndrome (9% STEMI, 44% non-ST-elevation). HPR to ADP after 600 mg clopidogrel loading occurred in 30% of patients (73±19 U vs 28±11 U; p<0.001) and was treated by prasugrel or ticagrelor (73%), or clopidogrel (27%) reloading (22±12 U; p<0.001). HPR to ADP after prasugrel loading occurred in 2% of patients (82±26 U vs 19±10 U; p<0.001) and was treated with ticagrelor (34±15 U; p=0.02). HPR to AA occurred in 9% of patients with a significant higher proportion in patients with HPR to ADP (22% vs 4%, p<0.001) and was treated with aspirin reloading. Definite ST occurred in 0.09% of patients (n=1); probable ST, myocardial infarction, cardiovascular death and MACE occurred in 0.19% (n=2), 0.09% (n=1) and 1.8% (n=18) of patients. TIMI major and minor bleeding did not differ between patients without HPR and individualised patients (2.6% for both). Conclusions: Individualisation of DAPT with MEA minimises early thrombotic events in an all-comers PCI population to an unreported degree without increasing bleeding. A randomised multicentre trial utilising MEA seems warranted. Trial registration number: http://www.clinicaltrials.gov ; NCT01515345 .